About High Rates of Biological Objects’ Freezing and Cooling in Cylindrical Containers When Immersing Them Into Liquid Nitrogen - Babenko, V. I.; Grischenko, V. I.; Dunayevskaya, A. V. (Problems of Cryobiology and Cryomedicine, 2006)
The heat transfer in multicomponent cryoprotective media under high cooling rates in cylindrical containers was experimentally and theoretically studied. As the medium model 1M phosphate buffer glycerol solution was used.